2023
DOI: 10.1101/2023.10.13.562224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell transcriptomic profiling identifies tumor-acquired and therapy-resistant cell states in pediatric rhabdomyosarcoma

Sara G Danielli,
Yun Wei,
Michael A Dyer
et al.

Abstract: Rhabdomyosarcoma (RMS) is a pediatric tumor that resembles undifferentiated muscle cells; yet the extent to which cell state heterogeneity and molecular features are shared with human development have not been fully ascribed. Here, we report a single-cell/nucleus RNA sequencing atlas derived from 72 datasets that includes patient tumors, patient-derived xenografts, primary in vitro cultures, and established cell lines. We report four dominant muscle-lineage cell states in RMS: progenitors, proliferative, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Neuronal populations were also distinctly identified in FP-RMS patient and orthotopic patient-derived xenograft tumor samples from single-cell RNA-sequencing 53 . Critically, upon chemotherapeutic treatment in these xenograft models, this neuronal population was transcriptionally enriched, which would support a hypothesis that neural pathways drive FP-RMS therapeutic resistance 52 .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Neuronal populations were also distinctly identified in FP-RMS patient and orthotopic patient-derived xenograft tumor samples from single-cell RNA-sequencing 53 . Critically, upon chemotherapeutic treatment in these xenograft models, this neuronal population was transcriptionally enriched, which would support a hypothesis that neural pathways drive FP-RMS therapeutic resistance 52 .…”
Section: Discussionsupporting
confidence: 56%
“…Single-cell RNA-sequencing of cell lines, orthotopic patient-derived xenograft models, and patient samples have shown that fusion-positive rhabdomyosarcoma consists of various cellular populations, including differentiated, ground, neuronal, progenitor, and proliferative [52][53][54][55][56] . To assess which transcriptional tumor cell populations PAX3::FOXO1 is initially activating, we completed gene set enrichment analysis to the markers of each of these cell populations.…”
Section: Pax3::foxo1 Activates Neural and Rhabdomyosarcoma Transcript...mentioning
confidence: 99%